The Effect of Workload and Work Discipline on Employee Performance at the Inspectorate of West Pasaman Regency - Putra, Endang Tirtana; Yuliza, Mai; Mantauv, Citra Suci; Efrida, Delfi (Journal of International Accounting, Taxation and Information Systems, 2025)
The study took place at the West Pasaman District Inspectorate and aimed to examine: (1) how workload affects performance, (2) how discipline affects performance, and (3) how workload and discipline together affect performance. All 67 Inspectorate employees comprised the population. Due to the small population size (under 100), saturated sampling was employed, using all 67 employees as the sample. Data was gathered through questionnaires and analyzed using multiple linear regression with SPSS For Windows version 21.00. The findings revealed that independent variables influenced the dependent variable as follows: (1) Workload positively and significantly affected employee performance (regression coefficient = 0.227, significance = 0.018, which is <0.05), (2) Discipline positively and significantly influenced employee performance (regression coefficient = 0.542, significance = 0.000, which is <0.05), (3) Workload and discipline combined positively and significantly impacted employee performance (regression coefficient = 32.552, significance = 0.000, which is <0.05). The R² value indicated that 57.1% of the variance was explained, while 42.9% was attributed to other variables not examined in this research.